A construção de uma identidade profissional - Pilatti, Ormil Alves [UNESP] (2014)
Based on personal documents that circulated within the Secretary of Education of the State of São Paulo, an elementary school mathematics teacher explores, in this paper, his ownproceedings, backed up by educational legislation, with the objective of understanding different levels of involvement of educational agents in face of official guidelines or recommendations for change in the public school system. Particularly related to the projects EscolaPadrão and Conselho de Escola, the analyzed episodes refer to municipal and statepublic schools units in the Capital and to another state public schools in the cities of Rio Claro, Santa Gertrudes and Cordeirópolis, covering a period extending from the early 1980s to the first years of the 2000s